The contribution of the ECU to exchange-rate stability. A comment - SARCINELLI, M. (PSL Quarterly Review, 2013)
The article is a brief note criticising some essential elements of Jager and De Jong’s The private ECU’s potential impact on Global and European exchange-rate stability (1988). The author provides three points of criticism which undermine that article’s analysis. Firstly, the ECU ought to be considered in all its functions of an international reserve currency and not only as an investment currency. Secondly, the restrictiveness of the assumptions underlying the portfolio approach make the authors’ outcome useless in practice. Thirdly, the outcome of their calculations favours the hypothesis that the ECU creates exchange-rate stability. JEL: F33, F36